Niveles de cuyaza en las características agronómicas y rendimiento de Lactuca sativa L. Lechuga, variedad Grand rapid, Zungarococha, Loreto.2024 - Da Silva Perez, Archely Thais del Rosario (2024)
The study investigated the effects of different levels of guinea pig manure (cuyaza) on the agronomic characteristics and yield of Lactuca sativa L. (lettuce), Grand Rapid variety, in the Zungarococha region, Loreto. A Completely Randomized Block Design with four treatments of cuyaza per hectare and four replications was employed. Parameters such as plant height, plant width, root length, stem length, stem weight, number of leaves per plant, leaf weight per plant, and total plant weight of lettuce were evaluated. The results indicated that treatment T4, with 30 tons per hectare of cuyaza, showed a significant improvement in multiple agronomic characteristics, including plant height, plant width, stem length, stem weight, number of leaves per plant, leaf weight per plant, and total plant weight of lettuce (p<0.001). Statistically significant differences were observed with treatment T4 in plant height (25.50 cm), stem length and weight (25.0 cm and 33 g, respectively), number of leaves (22 units), leaf weight per plant (84 g), and total plant weight (120 g). However, no significant differences were recorded in plant width and root length between treatments. These results suggest that the application of cuyaza can enhance the development and yield of lettuce, although it does not seem to significantly influence root length. A dose dependent response was observed in several variables, with treatments of 10 and 20 tons per hectare of cuyaza showing intermediate results compared to the 30 tons per hectare treatment.